Funding the New Biologics – What Can We Learn from Infliximab? The CCOHTA Report: A Gastroenterologist’s Viewpoint - Robert Hilsden (Canadian Journal of Gastroenterology)
The treatment of severe Crohn’s disease is difficult, and approximately 20% of patients do not respond to conventional therapy, including corticosteroids and immunosuppressives. Infliximab is one of the only treatments of proven efficacy in this group. Awareness of its benefits and risks is incomplete, because the drug has only recently been introduced and published research data are relatively sparse. Economic analyses help to evaluate the value of interventions that are both effective and expensive, but their validity is compromised by input data that involve questionable assumptions. They should not, therefore, be the only basis for funding decisions. Patients with severe Crohn’s disease are frequently unable to be gainfully employed and thus incur significant indirect costs. In a recent study by the Canadian Coordinating Office for Health Technology Assessment (CCOHTA), infliximab was deemed to not meet commonly accepted standards of cost effectiveness. This economic analysis did not incorporate indirect costs, and thus was inherently flawed and likely underestimated infliximab’s value. The CCOHTA report also used population data from a period of time during which treatment of Crohn’s disease was undergoing major transition. The study population was based in Minnesota and thus might not be applicable to Canada. Although they are routinely used in cost effectiveness models, quality-adjusted life-years gained are difficult to translate into practice, and the health care resources required to induce remission (or some other clinically meaningful result) might be a preferable measure. The CCOHTA report also did not include concomitant therapy with immunosuppressives, despite growing evidence for its benefit. Instead, it considered ‘usual care’, but, given the lack of effective treatment for many patients with Crohn’s disease, such an option constitutes ‘no care’ and continued suffering. Economic analyses should not be the only basis on which decisions regarding the funding of infliximab, or other new agents, are made.